A Preliminary Study on the Integrated UV/ozone/persulfate Process for Efficient Abatement of Atrazine. (1st November 2020) - Qin, Wenlei; Lin, Zhuang; Sun, Lei; Yuan, Xiangjuan; Xia, Dongsheng
ABSTRACT: The efficiency of the integrated UV/O3 /persulfate (PS) process was preliminarily explored with the emphasis on the pollutant removal performance and reactive radical contributions in this study. The results demonstrated that the integrated UV/O3 /PS process was significantly efficient with the pseudo-first-order rate constants of atrazine (ATZ) degradation increased by 18.7, 3.3 and 2.6 times compared to that in the O3 /PS, UV/O3 and UV/PS processes, respectively. Hydroxyl radical ( OH) and sulfate radical (SO4 − ) were corroborated to be the dominant reactive radicals in the UV/O3 /PS process via the radical scavenger experiments. The increase of PS dosage in the UV/O3 /PS process could contribute to the accelerated abatement of ATZ due to the enhanced formation of OH and SO4 − . The UV/O3 /PS process was demonstrated to be not susceptible to the impact of solution pH and could achieve a high removal efficiency of ATZ at each experimental pH condition (3.5 − 9.5). Compared to UV photolysis, O3 and OH, SO4 − was confirmed to play a more important role and account for 57.3%−72.1% elimination of ATZ at the investigated pHs. Moreover, the O3 /UV/PS treatment had a moderate resistance to the influence of water matrix components such as bicarbonate ions, providing a potential alternative for effective decontamination of organic contaminants in water treatment.